TOOLS FOR ANALYSIS OF FINANCIAL SECURITY INFLUENCE ON HOUSEHOLDS’ WELL-BEING IN UKRAINE - Зварич , Марта (Socio-economic relations in the digital society, 2019)
The tools for analysis of fi nancial security impact on households’ well-being in Ukraine are presented. The analysis using the multivariate regression model and the statistical equations of dependencies method has been conducted. The required growth of the level of fi nancial security instruments in order to increase population’s wellbeing is forecasted.The amount of total resources of one household per month in Ukraine has been chosen as a wellbeing indicator, as the material component remains the most important in determining the welfare of citizens. Among other indicators, there are: an average monthly wage, amount of deposits placed by households in Ukrainian banks, amount of average household’s total expenses for education per month. According to research results, the amount of deposits has the biggest infl uence on households’ well-being that can be explained by the popularity of this tool among the population, its reliability and the ability to generate income in the form of interest.